Textual statistics, conceptual mapping, bayesian network and landscape evaluation - Francesco Scarlatti; Giovanni Rabino (European Regional Science Association (ERSA), 2002)
Through the probabilistic reasoning is possible to take rational decisions even if there is limited information. The bayesian network is a probabilistic model that allows representing the uncertain knowledge in an given domain (of knowledge) in a graphical way. This method is not much used in planning yet, while it could be useful to analyse the uncertain variables that condition decisions in this field, e.g. the evaluation of the landscape elements to be protected. What are the elements, and the relationship, that represent the alpine landscape in the collective imagination? We have tried to find them using bayesian networks and textual statistics.
Keywords: 330